A Bibliometric Analysis of the Journal of Tropical Agriculture - Sarala, K. R. (Journal of Information and Knowledge, 1995)
Analyses the papers published in the Journal of Tropical Agriculture from 1989-94. Attempts to analyse the citations appended to the articles to find the most frequently cited periodicals by agricultural scientists of Kerala. A list of 30 most commonly cited periodicals has been prepared. In addition to this, identifies the types of publication cited. Authorship pattern of contributions, institution wise contributions and country wise distribution of frequently cited periodicals are also included.